An investigation into the wheat (Triticum aestivum L.) host response to Russian wheat aphid (Diuraphis noxia Kurd.) feeding - Fisher-Smith, Nadia (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhDAgric)--Stellenbosch University, 2023.